Effects of Different Intertillage Practices on Soil Biochemical Properties and Soybean Yield in Soybean Fields - Mingcong Zhang; Yanhong Zhou; Chenglin Li; Cheng Yuan; Mingfen Shan; Yuxin Fan; Zhongxia Yu; Linfeng Ren; Liu Cui; Chen Wang (Agronomy)
Heilongjiang Province, China, is a major soybean-producing area where low temperatures in early spring and poor soil moisture retention are the main limiting factors leading to low soybean yields. To improve land productivity, this study was conducted in Heilongjiang Province, China, from 2020–2021 via a field plot trial method, where four different intertillage treatments were set up in 2020: conventional intertillage (T1), early intertillage (T2), conventional subsoiling (T3), and early subsoiling (T4). In 2021, the effects of intertillage on soil biochemical characteristics and soybean yield formation were systematically analyzed under the T5 treatment (subsoiling at the stage of full development from the fourth to the fifth compound leaf) and the T6 treatment (soil culture at the stage of full development from the fourth to the fifth compound leaf). The results of the experiment revealed that deep loosening in advance improved the chemical properties of the soil. Compared with those of the T1 treatment, the contents of the organic carbon, total nitrogen, and available phosphorus and potassium in the early subsoiling treatments (T4, T5, and T6) were significantly increased. Intertillage time and depth had a strong influence on the soil microbial characteristics. Early medium intertillage could significantly increase the species abundance of bacteria and fungi in the soil, whereas subsoiling could increase the relative abundance ratio and uniformity of the dominant species. Compared with that in the T1 treatment, the yield of soybean in the T4 treatment was significantly greater, with yield increases ranging from 18.71% to 19.36%. In summary, the intertillage measures of one deep loosening and one medium soil cultivation at the stage of full development from the fourth to the fifth compound leaf and one large soil cultivation at the stage of full development from the sixth to the seventh compound leaf can be adopted on the basis of early deep loosening 4–5 d after soybean sowing to achieve high soybean yields. The results provide a theoretical basis for increasing the yield and efficiency of soybean fields under corn–soybean rotation, as well as innovation and development of cultivation systems